2019-novel coronavirus survey: knowledge and attitudes of hospital staff of a large Italian teaching hospital - Moro, Matteo; Vigezzi, Giacomo Pietro; Capraro, Michele; Biancardi, Anna; Nizzero, Paola; Signorelli, Carlo; Odone, Anna (Acta Biomedica Atenei Parmensis, 2020)
One week after the World Health Organization (WHO) declared the 2019 novel coronavirus (2019-nCoV) outbreak a global health emergency we conducted a survey to explore knowledge and attitudes on 2019-nCoV, recently renamed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), in a large cohort of hospital staff. A representative sample of 2,046 hospital staff of a large university hospital in northern Italy (54% healthcare workers and 46% administrative staff, overall response rate: 25%) was administered an online questionnaire: overall there is good knowledge on 2019-nCoV control measures. The mean of correct answers for questions on general aspects of 2019-nCoV epidemic was 71.6% for HCWs and 61.2% for non-HCWs. The mean of correct answers for questions on 2019-nCoV patient management was 57.8% among HCWs. Nevertheless, on recommended precautions, also among healthcare workers there is still much to do in order to promote effective control measures and correct preventive behaviours at the individual level